2011
DOI: 10.1080/13811118.2011.565265
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, Impulsivity, and Suicide Behavior: A Review of the Literature

Abstract: This article reviews the literature on the association between impulsivity aggression and suicide. The key words impulsivity, aggression, and suicide were entered into the pubmed, psychlit, and proqest databases. Significant articles were scrutinized for relevant information. Impulsivity and aggression are highly correlated with suicidal behavior across psychiatric samples, nosological borders, and non-psychiatric populations. Impulsivity and aggression are related but the nature of this relationship remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
216
5
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(261 citation statements)
references
References 148 publications
16
216
5
14
Order By: Relevance
“…Impulsivity has further been linked to suicidal behavior in numerous studies, though was usually mediated by a number of other risk factors (e.g., Kashden et al 1993;Beautrais et al 1999). More recently, Gvion and Apter (2011) reviewed the literature on aggression, impulsivity, and suicidal behavior. They concluded that, while there are inconsistencies and confusing findings given the interrelationship between aggression and impulsivity, the relationship between aggression, impulsivity, and suicidality is well-established.…”
Section: Impulsivity and Suicide Riskmentioning
confidence: 99%
“…Impulsivity has further been linked to suicidal behavior in numerous studies, though was usually mediated by a number of other risk factors (e.g., Kashden et al 1993;Beautrais et al 1999). More recently, Gvion and Apter (2011) reviewed the literature on aggression, impulsivity, and suicidal behavior. They concluded that, while there are inconsistencies and confusing findings given the interrelationship between aggression and impulsivity, the relationship between aggression, impulsivity, and suicidality is well-established.…”
Section: Impulsivity and Suicide Riskmentioning
confidence: 99%
“…15,16 It has been observed that lithium administration decreases impulsive aggressive behavior in men. 17 Possibly, higher levels of lithium in the drinking water decrease suicide rates among men by reducing impulsivity and aggression.…”
Section: Neurobiologymentioning
confidence: 99%
“…Its association with an increased risk for suicide in our bivariate analysis (Table 3) suggests personality might play a role in averse-life-event-related "impulsive" suicide. Previously, a number of studies showed that the most attributing factors of personality disorders to suicidal behaviors were impulsivity, aggression, and hostility [37,[75][76][77][78][79][80][81][82][83][84][85][86] . Since about half of suicides in China were unplanned and impulsive, the relationship between personality traits/disorder and suicides is worthy of further exploration with larger sample size studies.…”
Section: Issn 2372-5923mentioning
confidence: 99%